The God I don't understand : reflections on tough questions of faith - Wright, Christopher J. H., 1947- (Grand Rapids, Mich. : Zondervan, 2008)
If we are honest, we have to admit that there are many things we don't understand about God, especially in the face of terrible suffering and evil. Chris Wright offers reflections and encouragement from the Scriptures, so that those who are troubled by these tough questions can still sustain their faith. --from publisher description
The mystery of evil -- The offence of evil -- The defeat of evil -- The Canaanites : three dead ends -- The Canaanites : three frameworks -- The Cross : why and what? -- The Cross : how? -- The Cross : according to the scriptures -- Cranks and controversies -- The great climax -- The new beginning.
Includes bibliographical references (p. 222-[224]).
Keywords: Suffering -- Religious aspects -- Christianity; Good and evil; Theodicy; Faith